INTERROGATING HEROICS OF NIGERIAN CIVIL WAR IN ACHEBE’S THERE WAS A COUNTRY AND ADICHIE’S HALF OF A YELLOW SUN: A NEW-HISTORICIST APPROACH (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
The inciting narratives of the Biafran Civil War (1967–1970) likely provoke a case for the agitation for the actualisation of the Sovereign State of Biafra. The people of the defunct Biafra, mostly the Igbo, interpret the Federal Government’s ‘No Victor, No Vanquished’ proclamation as illusory. The result is the sustained quest for the liberation of Biafra through confrontations, with some calling for another civil war. This work, while analyzing the situation, observes that there were flaws in the war which would make its repeating tragic. It uses Achebe’s There Was a Country and Adichie’s Half of a Yellow Sun as primary texts. The data was further collated from works rendered by scholars with divergent views. The study is foregrounded on New Historicism. There is a conscious effort to deconstruct violent revolutionary approaches in the agitation, and state that the Igbo should rather explore the Biafran War innovations using their cultural resilience to make the South-East Region Nigeria’s commercial and technological hub. The research makes case for the intellectual re-birth of Biafra for scientific innovations and self-discoveries rather than a platform for another civil war.
Keywords: Biafra,NewHistoricism,Revolutionary,CulturalResilience,Innovations